Minimally Invasive vs. Open Surgery for Hallux Valgus: A Meta-Analysis - Ji, Linfeng; Wang, Ketao; Ding, Shenglong; Sun, Chengyi; Sun, Songmin; Zhang, Mingzhu (Frontiers in Surgery, 2022)
Purpose In recent years, minimally invasive surgery (MIS) for hallux valgus has emerged and gained popularity. To date, evidence on the benefits of MIS for hallux valgus is still controversial. This updated meta-analysis aimed to comprehensively evaluate the efficiency of MIS vs. open surgery for hallux valgus. Methods A systematic literature search of PubMed, Embase, and the Cochrane Library was performed. Two independent reviewers conducted data extraction and analyzed data with R software. Data were presented with risk ratio (RR) and standardized mean difference (SMD) along with 95% confidence interval (CI). Results A total of 22 studies in which there were 790 ft treated with the MIS procedure and 838 ft treated with an open procedure were included. The correction of sesamoid position was better in the MIS group. The post-operative distal metatarsal articular angle (DMAA) of the MIS group was lower. There was less pain at the early phase in the MIS group. The MIS group had a shorter surgery time and shorter hospitalization time compared with the open group. Our meta-analysis revealed no statistically significant difference in hallux valgus angle (HVA), first intermetatarsal angle (IMA), the first metatarsal shortening, the American Orthopedic Foot and Ankle Society (AOFAS) score, visual analog scale (VAS) score at the final follow-up or complication rate (when all studies were considered). When taking into consideration only randomized controlled trial (RCT), the AOFAS score was higher in the MIS group while HVA, IMA, DMAA, and complication rate remained no significance. Post-operative IMA of the MIS group was significantly lower when only studies reporting the second-generation (2G) MIS were included. When just studies adopting the third-generation (3G) MIS were included, the HVA and DMAA were lower in the MIS group. Conclusion The MIS procedures were more effective than open surgeries in the treatment of hallux valgus. Moreover, the MIS group achieved better radiologic and clinical outcomes compared with the open group.